2014
DOI: 10.1542/peds.2013-4036
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Cohort Study of Treatments and Hospital Outcomes in Neonatal Abstinence Syndrome

Abstract: OBJECTIVES: To compare pharmacologic treatment strategies for neonatal abstinence syndrome (NAS) with respect to total duration of opioid treatment and length of inpatient hospital stay. METHODS: We conducted a cohort analysis of late preterm and term neonates who received inpatient pharmacologic treatment of NAS at one of 20 hospitals throughout 6 Ohio regions from January 2012 through July 2013. Physicians managed NAS using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 22 publications
6
90
0
6
Order By: Relevance
“…Our study reinforces findings from smaller studies that standardizing care to infants with NAS improves clinical outcomes. 12 Over the last decade, the rate of NAS has grown substantially across the United States; however, LOS has remained stagnant. 2,6 Data suggest that hospitals vary in identification 8 and management 7,8 of infants with NAS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study reinforces findings from smaller studies that standardizing care to infants with NAS improves clinical outcomes. 12 Over the last decade, the rate of NAS has grown substantially across the United States; however, LOS has remained stagnant. 2,6 Data suggest that hospitals vary in identification 8 and management 7,8 of infants with NAS.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies from the Ohio NAS collaborative found that standardization, defined as stringent adherence to a treatment protocol, was more effective in reducing LOS than choice of a specific opioid (ie, methadone versus morphine). 12,16 In addition to protocol adherence, the evidence for treatment improvements for NAS is building. For example, data suggest that breastfeeding an infant who has NAS, when medically appropriate, 17 can decrease the need for NAS treatment 18 ; however, breastfeeding rates among infants with NAS are reportedly low.…”
Section: Discussionmentioning
confidence: 99%
“…The details of the protocol development, including nonpharmacologic and pharmacologic components, and prestudy training in standardization of Finnegan scoring and NAS treatment have been described previously. 17,18 Infants born at $34 weeks' gestation who were treated pharmacologically for NAS with methadone or morphine were included in the analysis. Infants who received iatrogenic opioid treatment or who had significant medical conditions necessitating surgical intervention or mechanical ventilation were not included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…16 We reported that use of a protocol with stringent weaning guidelines was associated with reductions in the duration of opioid exposure and length of hospital stay regardless of the treatment opioid. 17 Subsequently, 3 study centers without a standardized weaning approach adopted the standardized protocol.…”
Section: What This Study Addsmentioning
confidence: 99%
“…For example, the Ohio Perinatal Quality Collaborative standardized the approach to neonatal abstinence syndrome, showing an almost 10-day length of stay reduction (33% decline) for infants in centers that had a morphine weaning protocol versus those that did not. 66 In the longer run, such successes might be expected to be leveraged to even better Value, as partnership with hospital administration and payers allows sharing of the gains and reinvestment into ongoing quality improvement work.…”
Section: Quality Improvementmentioning
confidence: 99%